Immobilized Tio2/Chitosan Layered System Incorporating Reactive Red 4 Dye For The Photocatalytic Degradation Of Phenol - Sabar, Sumiyyah (2013)
An immobilized TiO2/chitosan layered system incorporating Reactive Red 4 (RR4) dye has been successfully fabricated, optimized and applied for the removal of phenol under a 45 W compact fluorescent lamp. The immobilized photocatalyst was prepared by adsorbing RR4 dye on chitosan (CS) sub-layer supported by glass plate, before being coated by TiO2 as the top layer (known as TiO2/RR4-CS/glass). Studies on the adsorption of RR4 dye by CS sub-layer showed that the highest RR4 uptake by CS/glass can be achieved at CS loading of 0.65 mg cm-2 (corresponding to 6.15 ± 0.13 μm in thickness), and pH 6.0 under room temperature (300 K). Thinner layer of CS/glass is favorable and more effective in adsorbing RR4 compared to thicker layer as it increases the surface area and porosity of CS. Langmuir and Freundlich isotherm models correlated well with the adsorption data with qmax of 86.2 mg g-1, suggesting that CS/glass is a viable mode for anchoring the dye.